Heterogeneity of malaria prevalence in alluvial gold mining areas in Northern Mato Grosso State, Brazil Heterogeneidade da prevalência de malária em garimpos do norte de Mato Grosso, Brasil - Alisson Flávio Barbieri; Diana Oya Sawyer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This paper analyzes factors affecting the risk of malaria among individuals working in wildcat gold mining camps (garimpos) in northern Mato Grosso State in the Brazilian Amazon. Historically, such mining camps have the locations with the highest malaria prevalence in the Brazilian Amazon. However, little attention has focused on understanding the disease from the internal perspective of the mining camps themselves, such as the mining population's characteristics and its spatial organization. This paper adopts a stepwise logistic model to identify spatial, occupational-exposure, and cultural factors that affect malaria prevalence. According to the results, differences among individuals working and/or living in the gold mining areas could produce different exposure to the disease and thus to different risk of malaria prevalence. Understanding these differences may provide an important tool for identifying risk profiles in the gold mining and related population and for informing programs for prevention and treatment of malaria in the Amazon. O artigo analisa fatores que afetam o risco de malária entre garimpeiros de ouro no norte de Mato Grosso, Brasil. Historicamente, os garimpos apresentam a maior prevalência de malária da Amazônia Legal brasileira. Entretanto, até o momento houve pouca investigação no sentido de compreender a doença desde a perspectiva interna dos próprios garimpos, ou seja, através das características da população garimpeira e da sua organização espacial. O artigo adota um modelo logístico stepwise para identificar fatores territoriais, culturais e de exposição ocupacional que afetam a prevalência da malária. Com base nos resultados, diferenças entre indivíduos que trabalham e/ou vivem nas áreas de garimpo poderiam produzir variações na exposição à doença, levando a um risco diferenciado de prevalência de malária. A compreensão dessas diferenças pode representar uma ferramenta importante para identificar perfis de risco na população do garimpo e do seu entorno, além de orientar programas para a prevenção e tratamento da malária na Amazônia.